Rekonseptualisasi Faktor Risiko dalam Kedokteran 2025 - Raymond R. Tjandrawinata (MEDICINUS, 2026)
The term “new risk factors” in the medical literature of 2025 rarely refers to the discovery of previously unknown disease determinants; rather, it reflects an epistemic shift in how risk is defined, measured, and interpreted. This perspectivehighlights how advances in objective measurement technologies, large-scale cohort analyses, and genetics-based causal approaches have brought renewed attention to factors that were previously under recognized or oversimplified. By examining examples such as multidimensionally measured sleep irregularity, wildfire smoke exposure as a cardiovascular determinant, chlorpyrifos pesticide exposure in neurodegenerative disease, and debates surrounding immune-relateddisease causality which assessed through Mendelian randomization, this article demonstrates that the “novelty” of riskfactors more often lies in the breadth of disease spectra and the depth of biological inference rather than in the variables themselves. Obesity and cancer are used as a conceptual framework to illustrate how clinical redefinition can reshape riskstratification and preventive strategies. This perspective argues that progress in modern medicine should not be measured by the expansion of risk factor lists, but by the capacity of scientific systems to assess risk with greater precision, contextual awareness, and orientation toward clinically meaningful outcomes.